2008
DOI: 10.4049/jimmunol.180.3.1670
|View full text |Cite
|
Sign up to set email alerts
|

The Receptor Tyrosine Kinase RON Represses HIV-1 Transcription by Targeting RNA Polymerase II Processivity

Abstract: Efficient HIV-1 transcription requires the induction of cellular transcription factors, such as NF-κB, and the viral factor Tat, which through the recruitment of P-TEFb enhances processive transcription. However, whether cellular signals repress HIV-1 transcription to establish proviral latency has not been well studied. Previously, it has been shown that the receptor tyrosine kinase RON inhibits HIV transcription. To gain insights into the biochemical mechanisms by which RON inhibits transcription we examined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
25
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 67 publications
2
25
0
Order By: Relevance
“…On the other hand, the idea that transcriptional interference would govern latent HIV-1 infection is somewhat in conflict with studies that report that paused RNA polymerase II (RNAP II) is found at the latent HIV-1 promoter (37,38,86). In addition, the involvement of upstream transcriptional control mechanisms in HIV-1 latency is suggested by a series of other studies.…”
mentioning
confidence: 48%
“…On the other hand, the idea that transcriptional interference would govern latent HIV-1 infection is somewhat in conflict with studies that report that paused RNA polymerase II (RNAP II) is found at the latent HIV-1 promoter (37,38,86). In addition, the involvement of upstream transcriptional control mechanisms in HIV-1 latency is suggested by a series of other studies.…”
mentioning
confidence: 48%
“…39 In humans, the overexpression of RON in monocytes and macrophages decreases the binding activity of NF-B and RNA polymerase II to the long terminal repeats of human immunodeficiency virus and inhibits proviral transcription. 40 In EBV-associated diseases, Renne et al demonstrated that 6 PTKs, including RON, are expressed in Hodgkin/Reed-Sternberg cells of Hodgkin lymphoma and suggested that RON may be involved in the pathogenesis of Hodgkin lymphoma. 41 Our results …”
Section: Discussionmentioning
confidence: 99%
“…No direct experimental evidence for this hypothesis has been provided, but restriction of P-TEFb and TFIIH, two important components of the actively transcribing RNA polymerase II complex, has been shown to contribute to a latent phenotype (11,12). To this end, paused RNA polymerase II complex has been found associated with the latent LTR promoter (11,(26)(27)(28)(29).…”
mentioning
confidence: 99%